Tumble bunnies - Lasky, Kathryn; Hafner, Marylin (Cambridge, Mass. : Candlewick Press, 2005)
Feeling inept in the team sports scheduled for his school's Gymboree, Clyde the rabbit develops his own event, a freestyle tumbling routine with a dazzling move called the "twirly burly."
1 9 13 23 29 39
Keywords: Sports -- Fiction; Sportsmanship -- Fiction; Tumbling -- Fiction; Rabbits -- Fiction